(3EOGQI GdHfhc GdESdGejI HYO YhdeI CShGb GdeGd (B/s - (3GdQOGOj, eMeO Hf eSdes ((3GdbGgQI(B: s (3GdefXeI GdYQHjI ddJfejI GdEOGQjI(B, s, 2005)
(3MOhO EOGQI GdHfhc GdESdGejI bHd YhdeI GdCShGb GdeGdjI, OhQ GdeDSSGJ GdNajI aj eSGQ GdfXGe GdeUQaj, EOGQI GdCUhd GdeGdjI HYO YhdeI CShGb GdeGd, cja JMGaX GdHfhc GdESdGejI Ydi COGA eJejR HYO YhdeI CShGb GdeGds
(3HHdjhZQGajG(B: (3U(B.163s
Keywords: (3CShGb GdeGds; (3GdHfhc GdESdGejIs